Etiology and Treatment of Renal Forniceal Rupture: A Single Center Experience - Hakan Erçil; Erbay Tümer; Aykut Buğra Şentürk; Ergün Alma; Umut Ünal; Mehmet Eflatun Deniz; Yalçın Kaya Evliyaoğlu; Zafer Gökhan Gürbüz (Journal of Urological Surgery)
Objective: To evaluate the clinical findings, treatment methods and outcomes of patients treated for renal forniceal rupture (RFR).